2007
DOI: 10.4049/jimmunol.179.4.2134
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Human Melanoma Antigen Expression by IFN-β

Abstract: Although many immunotherapeutic investigations have focused on improving the effector limb of the antitumor response, few studies have addressed preventing the loss of tumor-associated Ag (TAA) expression, associated with immune escape by tumors. We found that TAA loss from human melanomas usually results from reversible gene down-regulation, rather than gene deletion or mutation. Previously, we showed that inhibitors of MAPK-signaling pathways up-regulate TAA expression in melanoma cell lines. We have now ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…More recently, these discoveries were characterized by Dunn et al, who showed that IFN-b simultaneously augments TAAs (e.g., Melan-A/MART-1, gp100 and MAGE-A1) and HLA-class-I thus increasing the likelihood of improved immune recognition and cytotoxic killing of tumor targets, respectively. 64 The EMT is a process by which epithelial cells lose their polarization and cell-cell contacts and undergo remarkable morphologic changes switching from an epithelial cobblestone phenotype to an elongated fibroblastic phenotype. 65 The EMT provides for the evolution of cancer cells to the metastatic phenotype and contributes to their invasiveness, stemness and drug resistance.…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 99%
“…More recently, these discoveries were characterized by Dunn et al, who showed that IFN-b simultaneously augments TAAs (e.g., Melan-A/MART-1, gp100 and MAGE-A1) and HLA-class-I thus increasing the likelihood of improved immune recognition and cytotoxic killing of tumor targets, respectively. 64 The EMT is a process by which epithelial cells lose their polarization and cell-cell contacts and undergo remarkable morphologic changes switching from an epithelial cobblestone phenotype to an elongated fibroblastic phenotype. 65 The EMT provides for the evolution of cancer cells to the metastatic phenotype and contributes to their invasiveness, stemness and drug resistance.…”
Section: Cancer-intrinsic Effects Of Type-i-ifnsmentioning
confidence: 99%
“…Previous experience has suggested that a 3 day treatment period would be suitable for evaluation of antigen-enhancing effects of either small molecules or protein mediators, [25][26][27] and this time frame was also validated with the IL-2 assay coculture assay. 27 We chose to use a concentration of 10 mM for library screening.…”
Section: Assay Implementationmentioning
confidence: 99%
“…26 Since the transduced TCR used in the responding J-TCR-M1 cells is restricted by HLA-A2, the tumor cells were of necessity HLA-A2+ . We evaluated several candidate melanoma cell lines for the ability to stimulate the J-TCR-M1 cell line.…”
Section: Melanoma Stimulator Cell Linementioning
confidence: 99%
See 2 more Smart Citations